SIKAP MASYARAKAT HUKUM ADAT BALI TERHADAP PUTUSAN MK NO. 46/PUU-VIII/2010 TERKAIT KEDUDUKAN ANAK LUAR KAWIN - Ni Nyoman Sukerti; I Gst. Ayu Agung Ariani; I Ketut Sudantra (University of Udayana, 2015)
This study aimed to determine the knowledge of indigenous people of Bali against theConstitutional Court No.46 / PUU-VII / 2010, meaning the Constitutional Court rulingrelated to the child outside the mating position, to identify and analyze the attitudes ofindigenous communities Bali on the discharge of the Constitutional Court. This study is anempirical law with non-doctrinal approach (socio legal research).The results showed that indigenous people in general do not yet know Bali Court DecisionNo.46 / PUU-VII / 2010 was. Meaning beyond mating gives children the same rights aschildren born within marriage. Balinese people’s attitudes related to this decision, can beclassified into two: 1. Most accept the decision of the reason; children outside the matingstatus to clear, the mother can claim responsibility for the biological father of the child,the child is no longer despised in the family and society. 2. small Sebagain reject reason;children outside mating can cause problems in inheritance in biological father, contraryto the customary law of Bali, girls may prefer not to marry. The attitude of the indigenouspeoples of Bali pros and cons of the legal culture of society.Conclusion: Its meaning is to give children the right to marry outside the same as childrenborn within marriage. Balinese customary law community in general have not been awareof the Constitutional Court. Balinese people’s attitudes towards the Constitutional Courtruling pro and cons.